1981
DOI: 10.1002/jctb.280310185
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characteristics of rice hulls

Abstract: Evaluation of the thermal characteristics of rice hulls is described. Decomposition was negligible below 20O0C, but on heating above 200"C, the amount of volatile matter evolved increased steadily with increasing temperature up to 450°C, where > 90% of the total volatile matter was separated. Decompositionis rapid and is temperature dependent. The effect of temperature on the composition of the residues is also described. The carbon content of the residues increased while the oxygen and hydrogen content decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The third stage of decomposition (III) took place in the range of about 180-420°C, indicated by a sharp drop and a harsh peak in the TG and DTG curves, respectively. The mass loss of 47.4-60.7 % associated with this stage may be due to the removal of volatile matter [15]. Major decomposition occurred in the third (III) and fourth (IV) stages.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The third stage of decomposition (III) took place in the range of about 180-420°C, indicated by a sharp drop and a harsh peak in the TG and DTG curves, respectively. The mass loss of 47.4-60.7 % associated with this stage may be due to the removal of volatile matter [15]. Major decomposition occurred in the third (III) and fourth (IV) stages.…”
Section: Resultsmentioning
confidence: 94%
“…The specimens were cured at room temperature for 24 h after being removed from the mold. Since RHs are a very stable agricultural waste and the thermal decomposition of oven-dried husks was reported to be negligible below 200°C [15], they were dried in an oven at 105°C for 2 h and cooled in a desiccator. Use of PVA as a binder (adhesive) provides appropriate physical shape for characterization and application.…”
Section: Blend Preparationmentioning
confidence: 99%
“…Loss of weight continued slowly up to 500°C, which indicated that fine carbon was burned inside the silica pores. At 450°C, more than 90% of the total volatile matter was removed in the absence of air (Hamad 1981). Loss of weight was higher in the presence of air because of oxidation reactions.…”
Section: Fuelmentioning
confidence: 98%
“…The carbon content of the residue increased with pyrolysis temperatures between 200 and 500°C, whereas oxygen and hydrogen content decreased sharply. Pyrolysis of hull at 800-850°C for 7 min resulted in 37-40% residue containing 50% organic matter and 50% ash, but the char of combustion at 800°C in the presence of oxygen was 32%, consisting of 38% organic matter and 62% ash (Hamad 1981). Increasing air rates during combustion of rice hull in a fixed-bed furnace favored crystallization of silica, probably because of the higher combustion temperature (Hamad and Khattab 1981).…”
Section: Fuelmentioning
confidence: 98%
See 1 more Smart Citation